Utilisation of library websites for information literacy delivery in five selected universities in South Africa - Iyambo, Laimi (Library and Information Studies Centre (LISC), 2019)
The purpose of this study was to investigate how library web sites are used in delivering information literacy to a diversity of users in five selected universities in South Africa. Drawing from the Association of College and Research Libraries’ information literacy framework for higher education, the study sought to establish how information literacy content is designed into curricula and delivered. It further established tools that are used to deliver information literacy via library websites, strategies that are adopted in managing the process as well as the assessment tools used to test students’ learning of information literacy. Ultimately the study established the challenges librarians encounter when developing information literacy curriculum/content and using technologies on their web sites. This was done to improve the current practice of information literacy programme delivery at the University of Namibia libraries. The study was guided by Constructivism paradigm and the framework for Information Literacy Competency for higher education. The study employed a qualitative approach in which research participants were purposely selected. While a checklist was used to collect data from the library websites, interviews were used to collect data from librarians who are information literacy coordinators in their institutions. The study found that information literacy content encompasses the ability to identify an information need, locate, evaluate, use and manage information legally and ethically. Academic libraries used various strategies to inculcate information literacy skills among others includes Libguides, YouTube, videos, presentations in PDF and Microsoft Words, blog, Ask a Librarian and live Chat with a Librarian. Technologies such as Camtasia, Articulate software for videos, games, audios, quizzes creation, and Libguides are often used to develop and deliver information literacy content through library web-pages. Challenges that were highlighted by the librarians include inability to identify appropriate technologies to use and in most cases, librarians depend on IT personnel for assistance. The study will be useful to libraries which are in the process of developing online tutorials; it has potential to help librarians to identify appropriate technologies and processes involved to effectively develop tutorials that will eventually transform library websites into educational and learning platforms.